ANALISIS MUATAN HIGHER ORDER THINKING SKILL (HOTS) DALAM BUKU IPA KELAS VIII SMP BAB STRUKTUR DAN FUNGSI TUMBUHAN - Indriana Eka Suci; Martini Martini; Aris Rudi Purnomo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
This study aims to analyze HOTS content in two science books with the same chapter. HOTS content is seen from the indicators, sub-indicators, characteristics of material and questions. The research method uses descriptive methods. The type of analysis is content analysis. Determination of the sample using purposive sampling technique in the form of two books, namely the student’s book of Sciences SMP/MTs class VIII Semester 1 Curriculum 2013 revised edition 2017 published by the Ministry of Education and Culture as book 1 and the Science book TERPADU Junior High School Class VIII Curriculum 2013 revised edition 2016 published by Yudhistira as a book 2, in the same chapter, namely the Chapter Structure and Function of Plants. Data collection techniques use documentation study, careful reading, careful assessment of data sources. The results in book 1, there are 9 contents of HOTS material. The indicators that appear analyze (C4) 67%, evaluate (C5) 22%, and create (C6) 11%. There are 4 contents of HOTS questions. The indicators that appear analyze (C4) 75% and evaluate (C5) 25%. the percentage of HOTS in one chapter in this book is 41%. In book 2, there are 6 contents of HOTS material. The indicators that appear analyze (C4) 50%, evaluate (C5) 17%, and create (C6) 23%. There are 5 contents of HOTS questions. The indicators that appear analyze (C4) 60% and evaluate (C5) 40%. the percentage of HOTS in one chapter in this book is 20%